Melacak Akar Persoalan Bias Gender - Badrian, Badrian (Jurnal Muadalah, 2013)
Religion is often regarded as the cause of gender inequality pelanggengan, or at least, the interpretations of the teachings of religion have been rated have put women in the position of marginal and subordinate males. The issue is whether gender inequality is widespread in the religion derived from the nature of religion itself or whether it comes from the understanding , interpretation and religious thought impossible not influenced by tradition and culture or other causes. The reaction to inequality and injustice against women is what led to the emergence of the feminist movement among Muslim thinkers, such as Fatima Mernissi. According to Mernissi, oppression and discrimination against women in the Muslim community, according to Mernissi is not the nature of religion, or who termed Mernissi Islam treatise, because it is contrary to the universal doctrine, namely justice and the equality of men and women, but because it was created by a political system, including ideological, legal, and social culture. System patriarchal ideology and the interests of the political elite, which Mernissi termed by political Islam, it is Islam that distorts the Minutes.Keywords: gender, inequality, interpretation.